ISU PLAGIARISME DIGITAL DALAM DUNIA AKADEMIK DAN PROFESIONAL - Ery Nofrizal; Jasiah; Asmawati (CV. Adiba Aisha Amira, 2026)
Digital plagiarism has become an increasingly serious issue in the contemporary digital era, particularly within academic and professional environments. Rapid advances in information technology have enabled easy access to a wide range of digital resources, while simultaneously increasing the risk of copyright violations and the unauthorized use of others’ intellectual works. This paper aims to examine the concept of digital plagiarism, its various forms, underlying causes, and its impacts on academic integrity and professional credibility. The study also explores strategies to prevent and address digital plagiarism through ethical awareness, educational efforts, and the use of plagiarism detection technologies. This research employs a qualitative approach based on library research, drawing on academic journals, books, and expert opinions related to digital plagiarism and academic ethics. The findings indicate that a lack of understanding of citation practices, limited awareness of copyright issues, excessive academic pressure, and the ease of copying digital content are major factors contributing to digital plagiarism. Therefore, comprehensive education on digital ethics, strict institutional policies, and the effective use of plagiarism detection tools are essential to minimizing plagiarism practices in academic and professional contexts